O prawie III Rzeszy Niemieckiej w Polsce (1939–1945) - Salmonowicz, Stanisław (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Studies on the legal situation of Poles under German occupation during the Second World War have been conducted in Poland for a long time. For many years, however, they have not sufficiently addressed the problem of the fundamental difference between the legal positions of Poles and Western Europeans during the German occupation. The book published in 2017 by Maciej Mitera, entitled Ordinary Fascism. The Legal Position of the Citizens of the Second Polish Republic in the General Government 1939–1944 is an opportunity to sort out the concepts of the law applied to Poles under German occupation. In addition to general regulations, laws, and decrees issued by Governor Hans Frank, the German authorities issued several general orders or prohibitions which defined the legal status of General Government residents. These regulations differentiated the legal position of various population groups in the territory of the General Government, segregating people and excluding certain groups from normal social life. At the same time, German regulations were the basis for the exploitation of society and served the purpose of confiscating its property, and finally — extermination. Further research is needed to gain a complete picture of the German occupation of Polish lands.
Keywords: okupacja hitlerowska; prawo hitlerowskie; Generalne Gubernatorstwo; położenie prawne Polaków pod okupacją